2016
DOI: 10.1371/journal.pone.0156277
|View full text |Cite
|
Sign up to set email alerts
|

Fucosylated Glycans in α1-Acid Glycoprotein for Monitoring Treatment Outcomes and Prognosis of Cancer Patients

Abstract: One standard treatment option for advanced-stage cancer is surgical resection of malignant tumors following by adjuvant chemotherapy and chemoradiotherapy. Additionally, neoadjuvant chemotherapy may be applied if required. During the time course of treatments, patients are generally followed by computed tomography (CT) surveillance, and by tumor marker diagnosis. However, currently, early evidence of recurrence and/or metastasis of tumors with a clinically relevant biomarker remains a major therapeutic challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 77 publications
0
34
0
Order By: Relevance
“…Whereas, enzymatic and molecular analyses of serum α1,3fucosyltransferase both in wild type and FUT6-deficient individuals together with those of fucosylation in AGP revealed that fucosylation of the AGP molecule was carried solely by the FUT6 gene-encoded hepatic α1,3fucosyltransferase, and that no α1,6, α1,2 or α1,4 but only α1,3fucosylated linkage was present in the AGP molecule 22–24 . Furthermore, we developed a MALDI-TOF-MS system with a novel operation software (AGPAS) to analyze glycan structures of AGP comprehensively and determined a relative abundance of α1,3fucosylated glycans with tri- and tetraantennary glycan chains in AGP (FUCAGP) 25,26 . Accordingly, it was found, for the first time, that α1,3fucosylated AGP could be an appropriate marker of disease progression and prognosis in various cancer patients, and that abnormally high levels of FUCAGP were found in patients with esophagus, stomach, lung, breast, liver, pancreas, colon and rectum carcinomas who had a poor prognosis 25,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, enzymatic and molecular analyses of serum α1,3fucosyltransferase both in wild type and FUT6-deficient individuals together with those of fucosylation in AGP revealed that fucosylation of the AGP molecule was carried solely by the FUT6 gene-encoded hepatic α1,3fucosyltransferase, and that no α1,6, α1,2 or α1,4 but only α1,3fucosylated linkage was present in the AGP molecule 22–24 . Furthermore, we developed a MALDI-TOF-MS system with a novel operation software (AGPAS) to analyze glycan structures of AGP comprehensively and determined a relative abundance of α1,3fucosylated glycans with tri- and tetraantennary glycan chains in AGP (FUCAGP) 25,26 . Accordingly, it was found, for the first time, that α1,3fucosylated AGP could be an appropriate marker of disease progression and prognosis in various cancer patients, and that abnormally high levels of FUCAGP were found in patients with esophagus, stomach, lung, breast, liver, pancreas, colon and rectum carcinomas who had a poor prognosis 25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we developed a MALDI-TOF-MS system with a novel operation software (AGPAS) to analyze glycan structures of AGP comprehensively and determined a relative abundance of α1,3fucosylated glycans with tri- and tetraantennary glycan chains in AGP (FUCAGP) 25,26 . Accordingly, it was found, for the first time, that α1,3fucosylated AGP could be an appropriate marker of disease progression and prognosis in various cancer patients, and that abnormally high levels of FUCAGP were found in patients with esophagus, stomach, lung, breast, liver, pancreas, colon and rectum carcinomas who had a poor prognosis 25,26 . It was of particular interest that recurrence and/or metastasis occurred in patients who had been undergoing chemotherapies and/or radiation after operation was detected by elevated levels of FUCAGP in advance before their determinations with computerized tomography (CT) scans and diagnoses with conventional tumor markers.…”
Section: Introductionmentioning
confidence: 99%
“…It was an effective study of a disease such as lung cancer for which tissue diagnosis is difficult before treatment . In addition, lectins have been studied as predictors of recurrence and the prognosis . However, the actual roles of lectins and their binding glycoproteins have not been clarified in any research.…”
Section: Discussionmentioning
confidence: 99%
“…23 In addition, lectins have been studied as predictors of recurrence and the prognosis. 24 However, the actual roles of lectins and their binding glycoproteins have not been clarified in any research. In this study, our results suggested that HHL might be associated with infiltration of SCC, which means it could become a marker of the prognosis or relapse in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In the healthy gut, the resident bacteria occupy intestinal colonization niches. A major function of the commensal microbiota is the proliferation and colonization of incoming enteric pathogens as well as opportunistic pathobionts through multiple mechanisms [10,11].…”
Section: Introductionmentioning
confidence: 99%